A mechanism for localized dynamics-driven activation in Bruton's tyrosine kinase. Issue 8 (18th August 2021) - Qiu, Simei; Liu, Yunfeng; Li, Quhuan
Abstract : Bruton's tyrosine kinase (BTK) plays a vital role in mature B-cell proliferation, development and function. Its inhibitors have gradually been applied for the treatment of many B-cell malignancies. However, because of treatment-associated drug resistance or low efficacy, it is urgent to develop new inhibitors and/or improve the efficacy of current inhibitors, where finding the intrinsic activation mechanism becomes the key to solve this problem. Here, we used BTK T474M mutation as a resistance model for inhibitors to study the mechanism of BTK activation and drug resistance by free molecular dynamics simulations. The results showed that the increase of kinase activity of T474M mutation is coming from the conformation change of the activation ring and ATP binding sites located in BTK N-terminus region. Specifically, the Thr 474 mutation changed the structure of A-loop and stabilized the binding site of ATP, thus promoting the catalytic ability in the kinase domain. This localized dynamics-driven activation mechanism and resistance mechanism of BTK may provide new ideas for drug development in B-cell malignancies.